The Psychological Contributions of Natural Site Experiences in Kastamonu, Turkey - Sakici, Cigdem (Kamla Raj Enterprises, 2014)
The present paper was carried out on 47 nature lover participants from different cities in Turkey that were brought together within the framework of the Nature Training Project and whose demographic backgrounds (age, education level, profession, income level, gender) were completely different from one another and who did not know one another previously. The participants were trained for one week by a number of expert trainers about nature on both theoretical and applied levels at the Pinarbasi district of Kastamonu. They were taken to the difficult-to-access untouched areas, where different geological formations can be found, to areas full of historic structures, waterfalls, canyons, caves, and national parks, and were informed about these areas and their flora and fauna. They were asked to listen to the natural sounds (wind, birds, water, leaves, etc.), to smell the soil and plants and to perceive different colors in nature. It was aimed to identify the changes in the moods of these people as well as the characteristics of nature that resulted in these changes. Besides, the present paper aims to determine which activities these people enjoyed the most in natural sites. The obtained results informed that natural site experiences had a positive impact on the participants, and helped them gain awareness, release stress, and achieve a more positive state of mind.
Keywords: 4. Education; 15. Life on land; 16. Peace & justice